2010
DOI: 10.4021/jocmr2010.03.261e
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Chronic Obstructive Pulmonary Disease Patients Admitted in Hospital With Acute Exacerbation

Abstract: BackgroundPatients with Chronic Obstructive Pulmonary Disease (COPD) are frequently hospitalized with an acute exacerbation. Patients with COPD often lose weight. Consequently, deterioration in nutritional status (loss of lean body mass) is a likely repercussion of acute exacerbation in hospitalized COPD patients. The study was carried out to assess the nutritional status of COPD patients with acute exacerbation, during the period of hospital admission, and to evaluate the relationships between the nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Numerous studies, however, reported on the association between nutritional status and healthcare utilisation, focusing on patients hospitalised for a COPD exacerbation or predictors thereof. The studies showed that being undernourished in COPD is likely to be associated with longer in-patient hospital stays [107,108], a higher probability of being readmitted [62,109] and an increase in healthcare utilisation [110] in comparison with normally nourished patients. Three randomised controlled trials in COPD investigated the effects of nutritional supplementation on healthcare utilisation and/or costs [65,76,111].…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…Numerous studies, however, reported on the association between nutritional status and healthcare utilisation, focusing on patients hospitalised for a COPD exacerbation or predictors thereof. The studies showed that being undernourished in COPD is likely to be associated with longer in-patient hospital stays [107,108], a higher probability of being readmitted [62,109] and an increase in healthcare utilisation [110] in comparison with normally nourished patients. Three randomised controlled trials in COPD investigated the effects of nutritional supplementation on healthcare utilisation and/or costs [65,76,111].…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…Adult malnutrition is a significant health problem in India. The prevalence of malnutrition ranges from 20% to 60% in hospitalised patients (Chauhan et al ., ; Shirodkar & Mohandas, ; Gupta et al ., ; Karmakar et al ., ) and a similar magnitude of malnutrition has been reported in community‐dwelling adults (Arlappa et al ., ; Bose et al ., ; Das & Bose, ). Malnutrition leads to negative consequences for patients and economic burden for health care facilities (Amaral et al ., ; Loser, ; Barker et al ., ; Guest et al ., ), both of which add to the overall healthcare costs from malnutrition‐related diseases within India.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, a hospital based study found that 83% of COPD patients were found to have BMI < 18 kg/ m 2 in the city of Luknow in North India ( 128 ). However, the loss of body weight can also be a consequence rather than a risk factor of progression of the disease as BMI was found to be negatively correlated with duration of hospital stay (r = -0.0103, p = 0.03) ( 128 ). Th e positive correlation between oxidative stress and BMI in COPD status and predicted % of FEV 1 has also been reported.…”
Section: Other Risk Factorsmentioning
confidence: 99%